Spatial and Seasonal Distribution of Nitrate and Phosphate Contamination in Groundwater in Wadi Al-Tarfawi, Northeastern Libya - Al-haen, Mohammed; Al-Haen, Issa; Abdullah Abdullah; Habeeb Abdulqadir; Ahmed Mohamed; Ahmed Alabed (AlQalam Journal of Medical and Applied Sciences, 2026)
This study aimed to evaluate the quality of groundwater in Wadi Al-Tarfawi, Libya, through the assessment of its physicochemical characteristics, with particular emphasis on nitrate and phosphate concentrations and their spatial and seasonal variations in relation to international health standards. Groundwater Wells were collected from five wells during the summer and winter seasons of 2025, with three replicates per well. Laboratory analyses were conducted following standard methods and included measurements of temperature, pH, total dissolved solids (TDS), and electrical conductivity (EC), in addition to the determination of nitrate and phosphate concentrations using spectrophotometric techniques. Descriptive statistical analysis and one-way ANOVA were applied to assess seasonal differences at a significance level of (p < 0.05). The results revealed clear spatial and seasonal variability in the studied parameters. Groundwater temperature ranged between 22 and 27°C, while pH values varied from 7.2 to 7.9, all within locally and internationally permissible limits. Total dissolved solids ranged from 595 to 1102 mg/L, whereas the highest electrical conductivity reached 2285 µS/cm during the summer season. Phosphate concentrations recorded a maximum value of 0.77 mg/L in summer, exceeding the recommended global guideline (0.5 mg/L) in several wells, while the minimum value (0.06 mg/L) was observed in winter. Nitrate concentrations ranged from 21 to 64 mg/L, with exceedances of the WHO drinking water limit (45 mg/L) detected in two wells during the summer season. These findings indicate the influence of intensive agricultural activities, shallow groundwater depth, and local hydrogeological conditions on groundwater quality. The study highlights the need for continuous monitoring programs and improved fertilizer management practices to protect groundwater resources and public health.